2015
DOI: 10.1098/rstb.2014.0148
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing innate immunity and vaccine responses in infancy

Abstract: Despite significant progress in reducing the burden of mortality in children under the age of five, reducing mortality in newborns remains a major challenge. Infection plays a significant role in infant deaths and interventions such as early vaccination or antenatal immunization could make a significant contribution to prevention of such deaths. In the last few years, we have gained new insights into immune ontogeny and are now beginning to understand the impact of vaccines, nutrition and environmental factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 39 publications
(45 reference statements)
1
24
0
Order By: Relevance
“…Cytomegalovirus infection is acquired early in life by most infants in Africa and has a profound effect on the immune system ( 101 103 ). Other factors could include nutrition, genetics, and season of birth ( 104 , 105 ).…”
Section: Factors That Affect Bcg-induced Immune Responsesmentioning
confidence: 99%
“…Cytomegalovirus infection is acquired early in life by most infants in Africa and has a profound effect on the immune system ( 101 103 ). Other factors could include nutrition, genetics, and season of birth ( 104 , 105 ).…”
Section: Factors That Affect Bcg-induced Immune Responsesmentioning
confidence: 99%
“…This role of CTH as antigen extracted from A. mellifera to increase antibodies production in young goats could be linked to the factors innate immunity and vaccine responses in neonates as described by Kampmann and Jones (2015) which were affected by the type of vaccine, timing of vaccination, location, microbiome, co-infections, maternal factors, host genetics and pattern recognition receptors. More over an effort to increase the goat's immunity by antigen combined with adjuvant has been performed by Iqbal et al (2016) in young goats: They result showed a positive response to reject the parasite insect in the animal tested by using this combination substances.…”
Section: Resultsmentioning
confidence: 99%
“…The nonspeci c effects of vaccines have long been dismissed or minimized, but these biological phenomena should not be ignored, particularly considering that the innate immune system reveals some adaptive characteristics. Thus, it is now urgent that the effects of vaccination should be viewed in a much more systematic and open-minded manner [2,3]. Worryingly, a transitory state of immunosuppression subsequently to vaccination has been described in several studies [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Sentinel cells of the innate immune system, such as macrophages and neutrophils, represent the rst line of defense against a drastic exposure to infectious pathogens in neonates. The innate immune system in turn stimulates the adaptive immune response, and as a result the stimulation of immune memory responses [3,14,15]. Thus, another factor that should be investigated is the optimal age for vaccination [11,[16][17][18][19] because age has an impact on an animal's immune response [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation